2022
DOI: 10.3390/microorganisms10020322
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Implicated in Antibiotic Resistance in Helicobacter pylori Patients

Abstract: Helicobacter pylori is a common gastric pathogen associated with multiple clinical syndromes, including cancer. Eradication rates of H. pylori remain suboptimal despite the progress made in the past few decades in improving treatment strategies. The low eradication rates are mainly driven by antibiotic resistance of H. pylori. Non-invasive molecular testing to identify patients with antibiotic-resistant H. pylori represents a promising therapeutic avenue, however this technology currently remains limited by av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 85 publications
(141 reference statements)
0
14
0
1
Order By: Relevance
“…Also, in a Korean study, they didn't find a relationship between the prevalence of metronidazole resistance and age (Lee et al, 2013). In contrast, metronidazole resistance was significantly associated with age in an American and Japanese studies (Okuda et al, 2019;White et al, 2022).…”
Section: Epidemiological Factors and Metronidazole Resistancementioning
confidence: 90%
“…Also, in a Korean study, they didn't find a relationship between the prevalence of metronidazole resistance and age (Lee et al, 2013). In contrast, metronidazole resistance was significantly associated with age in an American and Japanese studies (Okuda et al, 2019;White et al, 2022).…”
Section: Epidemiological Factors and Metronidazole Resistancementioning
confidence: 90%
“…A recent nationwide study demonstrated that the H. pylori eradication rate of concomitant therapy is significantly higher than that of sequential therapy (91.8% vs 86.1%, P < 0.001)[ 54 ]. Antibiotic overuse and the emergence of multidrug-resistant H. pylori may be problematic for concomitant therapy[ 55 ].…”
Section: Recommended H Pylori Regimensmentioning
confidence: 99%
“…Several clinical factors have been associated with antibiotic-resistant H. pylori , including previous antibiotic exposure, older age, female sex, geographic region, ethnicity, alcohol consumption, and non-ulcer dyspepsia [ 63 ]. However, the most important risk factor associated with antibiotic resistance is previous antibiotic use [ 64 ].…”
Section: Clinical Determinants Of Antibiotic Resistancementioning
confidence: 99%
“…Furthermore, antibiotic resistance to H. pylori can vary between ethnic groups even in the same geographic area, suggesting differences in access to healthcare and the presence of genetic and cultural factors [ 63 ].…”
Section: Clinical Determinants Of Antibiotic Resistancementioning
confidence: 99%